2007
DOI: 10.1097/wnr.0b013e328013e3eb
|View full text |Cite
|
Sign up to set email alerts
|

Increased visual dependence and otolith dysfunction with alcohol intoxication

Abstract: Alcohol intoxication affects the vestibular system and balance control in many ways. We have investigated how acute, moderate (blood alcohol concentrations of 0.06+/-0.01%), and high (0.10+/-0.02%) alcohol intoxication affects the ability to perceive the visual horizontal and vertical and the visual field dependence measured with the rod and frame tests in 24 healthy participants. Alcohol ingestion impaired the ability to use gravitational vestibular cues when determining the visual vertical and horizontal, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…Another explanation could be that the information provided by vision is distorted by alcohol intoxication effects on the vestibular system through visual-vestibular interactions. Hafström and colleagues reported that spatial orientation was increasingly more dependent on visual information with increasing alcohol intoxication (Hafstrom et al, 2007). Hence, if the CNS regards vision as a reliable source for spatial orientation even when the information is unreliable, there could be larger proportional destabilizing effects of alcohol intoxication with eyes open compared with eyes closed, as revealed in the present study.…”
Section: Visual Contribution Is Changed By Alcohol Intoxicationsupporting
confidence: 62%
See 2 more Smart Citations
“…Another explanation could be that the information provided by vision is distorted by alcohol intoxication effects on the vestibular system through visual-vestibular interactions. Hafström and colleagues reported that spatial orientation was increasingly more dependent on visual information with increasing alcohol intoxication (Hafstrom et al, 2007). Hence, if the CNS regards vision as a reliable source for spatial orientation even when the information is unreliable, there could be larger proportional destabilizing effects of alcohol intoxication with eyes open compared with eyes closed, as revealed in the present study.…”
Section: Visual Contribution Is Changed By Alcohol Intoxicationsupporting
confidence: 62%
“…Two participants from this group were excluded: one for not reaching intended BAC and one due to failing an otolith test (Hafstrom et al, 2007). The final study group consisted of 25 participants, 13 women and 12 men of mean age 25.1 years (range 19-41), mean height 1.75 meters (range 1.60-1.92), mean weight 68.8 kilograms (range 50.05-106.3) and mean BMI 22.2 (range 17.9-30.7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study aimed to investigate alcohol-related effects on postural control and adaptation in the descending phase at exact, pre-specified, alcohol levels using the latest generation of precise alcohol breath analyzers. This report is part of a larger study concerning the effects of alcohol on vestibular [17], oculomotor [18] and postural systems [19,20].…”
Section: Introductionmentioning
confidence: 98%
“…Studies of ocular counterrolling have shown a small decrease in torsion after alcohol consumption (Diamond and Markham, 2008;Markham and Diamond, 2006). In contrast, there does not appear to be an effect of alcohol on the perception of subjective visual vertical (SVV) either during standard test administration (Zingler et al, 2003) or during eccentric rotation (Lindgren et al, 1998), though there tends to be an alcohol-related increase in visual field dependence on the rod and frame test (Hafstrom et al, 2007).…”
Section: Introductionmentioning
confidence: 99%